Acute Low-Dose Hydralazine-Induced Lupus Pneumonitis - Sarah K. Holman; Donique Parris; Sarah Meyers; Jason Ramirez (Case Reports in Pulmonology)
A 35-year-old female was started on hydralazine 10 mg orally three times a day for treatment of postpartum hypertension. Three months later, after multiple unsuccessful courses of prednisone and antibiotics for presumed pneumonia and asthma exacerbations, her respiratory symptoms progressed in severity and she developed resting hypoxia. Previous diagnostic work-up included spirometry with a restrictive pattern, chest CT showing bilateral basilar consolidation, negative BAL, and nonspecific findings on lung biopsy of mild inflammatory cells. Review of systems was positive for arthralgia, lymphadenopathy, paresthesia, and fatigue that began four weeks after starting hydralazine. A clinical diagnosis of hydralazine-induced lupus (HIL) with pneumonitis was made. Antihistone antibodies were positive supporting a diagnosis of HIL. Management included cessation of hydralazine and a prolonged steroid taper. Within days, patient began improving symptomatically. Six weeks later, CT chest showed complete resolution of infiltrates. Genetic testing revealed she was heterozygous for N-acetyltransferase 2 (intermediate acetylator). Drug-induced lupus should be considered in patients with lupus-like symptoms taking medications with a known association. While the majority of HIL cases occur with high doses and prolonged treatment, cases of low-dose HIL have been reported in patients who are slow acetylators.